(untitled) - Mahnaz Seyedoshohadaee; Shima Parnian; Hamid Haghani; Mohammad Sadegh Sargolzaei (University of Ostrava, 2021)
Aim: One of the psychological interventions that help patients effectively deal with the problems and challenges of daily life is life skills training. So determining the effect of life skills training on the coping of people with multiple sclerosis (MS) was the aim of this study. Design: A quasi-experimental study. Methods: The research was conducted with a sample of 80 people with MS attending the Tehran MS Association in 2017. The intervention group received four one-hour life skills training sessions and the control group received only routine care. To contrast the results between the two groups and the findings before and after the intervention, the independent t-test and paired t-test, respectively, were used. Results: Most of the respondents in both the intervention and control groups (55.0% and 57.5%, respectively) were males. There was no significant disparity in terms of coping with MS between the two groups before the intervention (p < 0.05) but a significant disparity after the training (p < 0.01). Conclusion: Applying life skills as effective and useful training was the achievement of this study. Therefore, application of the life skills training program is recommended for MS patients.